HUBUNGAN KECERDASAN INTERPERSONAL DAN MOTIVASI BELAJAR INTRINSIK TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN GEOGRAFI DI SMAN UNGGUL ACEH TIMUR - Najah, Safinatun; Aziz, Daska; Zalmita, Novia (Universitas Syiah Kuala, 2024)
The subject of Geography aims to develop basic concepts related to spatial patterns, the utilization of natural resources, and the surrounding environment. However, at SMAN Unggul Aceh Timur, many students have low self-confidence despite having good academic achievement. This study aims to determine the relationship between interpersonal intelligence and intrinsic learning motivation with academic achievement among 11th-grade social science students in Geography. This study used a quantitative approach with a correlational research design. The population consisted of 24 students, and data were collected through questionnaires and analyzed using multiple regression analysis. The obtained regression equation was Y = 18.871 + 3.993X + 3.970X. The correlation coefficient between interpersonal intelligence and academic achievement was -0.335, while the correlation between intrinsic learning motivation and academic achievement was -0.340, both categorized as weak. The multiple correlation coefficient was 0.363, indicating a low relationship, with a determination coefficient of 13.2%, meaning that only 13.2% of the variation in academic achievement is influenced by interpersonal intelligence and intrinsic learning motivation, while 86.8% is affected by other factors. The hypothesis test results showed that Fcount (1.609) Ftable (3.47), meaning that H is accepted, indicating no significant relationship between interpersonal intelligence and intrinsic learning motivation with academic achievement in Geography among 11th-grade social science students at SMAN Unggul Aceh Timur. This suggests that other factors, such as teaching methods, learning environment, parental support, interests, and talents, have a greater impact on students' academic achievement. Further research is needed to explore more dominant factors influencing students' learning outcomes.